(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article conducted a study of e-commerce systems in Uzbekistan on the example of Foton JSC. During the study, the legal framework, infrastructure and practical aspects of e-commerce in the activities of Foton JSC were studied. The results show that e-commerce is developing rapidly in Uzbekistan, but there are a number of problems and recommendations for solving and further development of these problems are presented.